Escrituras en escena: Teresa de la Parra y el teatro de lo íntimo - Nathalie Bouzaglo (Les Cahiers ALHIM)
This article analyzes how Venezuelan writer Teresa de la Parra stages her place within the literary world in the face of the boundaries and potentialities of gender and nationality of her time. It examines the role of the pseudonym in her early career, the iconic role played by Sarah Bernhardt's excentricities as key influences in her writing. Teresa de la Parra uses the international projection of her work to confront the limitations surrounding vanity and frivolity that define Ifigenia's reception in Venezuela. She distances herself from Venezuelan readers and, at the same time, proposes to rethink the Venezuelan nation in terms of a Hispanic-American project. The essay shows how Teresa de la Parra strategically participates in the editorial politics of the lettered city and manages to become a celebrity at a time when fame was not easy for a Latin American woman in the early 20th century.